2012
DOI: 10.1007/s13311-012-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Co-Occurring Attention Deficit/Hyperactivity Disorder and Autism Spectrum Disorder

Abstract: Interest in the co-occurrence of attention deficit/ hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) has grown in the last decade. Research on clinical populations supports the frequent co-occurrence of ADHD traits (e.g., hyperactivity) in individuals with ASD and ASD traits (e.g., social communication deficits) in individuals with ADHD. Similar trends in co-occurring traits have been observed in population-based samples, as well as family and genetic studies of affected individuals. Despite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 123 publications
(168 reference statements)
1
84
0
4
Order By: Relevance
“…In other studies co-occurring ADHD and ASD seem to be less responsive to standard treatments for either disorder than individuals with "pure" forms of the disorders 19 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In other studies co-occurring ADHD and ASD seem to be less responsive to standard treatments for either disorder than individuals with "pure" forms of the disorders 19 .…”
Section: Discussionmentioning
confidence: 85%
“…A small placebo-controlled efficacy trial indicated positive effects in terms of the reduction of hyperactivity and impulsivity, but not inattention in youth with ASD, with fewer adverse events as compared to stimulant trials 26 . Additional research using parents and teachers as informants showed significant reductions in ADHD symptoms among children with ADHD and ASD and side effects were rated as "minimally present" 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The first challenge, presented by Amar Mehta, MD, explores the impact an ASD diagnosis may have on a patient's family, and the importance of establishing a strong alliance with caregivers, as denying the truth of a diagnosis can deprive a child of much needed early intervention. Attendance to caregiver strain can also improve the outcome of the entire family.…”
Section: Impact Of Patient Diversitymentioning
confidence: 99%
“…The need for effective interventions in these populations is just starting to be addressed. Davis and Kollins [15] review pharmacological and psychosocial interventions, (this issue), and suggest future research areas based on current gaps in the knowledge regarding the co-occurrence of ADHD and ASD symptoms.…”
mentioning
confidence: 99%